1998
DOI: 10.1007/s00585-998-0821-3
|View full text |Cite
|
Sign up to set email alerts
|

Incoherent scatter radar observations of AGW/TID events generated by the moving solar terminator

Abstract: Abstract. Observations of traveling ionospheric disturbances (TIDs) associated with atmospheric gravity waves (AGWs) generated by the moving solar terminator have been made with the Millstone Hill incoherent scatter radar. Three experiments near 1995 fall equinox measured the AGW/TID velocity and direction of motion. Spectral and cross-correlation analysis of the ionospheric density observations indicates that STgenerated AGWs/TIDs were observed during each experiment, with the more-pronounced eect occurring a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 18 publications
7
64
2
1
Order By: Relevance
“…3a and d), and the corresponding parameters (T , V z , and λ z ) are in agreement with those found by Klausner et al (2009). The UT of such signatures suggests that for these cases GWs are excited by the solar terminator passage (Somsikov and Ganguly, 1995;Galushko et al, 1998). On the other days, not characterized by RSF occurrence (Fig.…”
Section: Discussion and Summarysupporting
confidence: 86%
“…3a and d), and the corresponding parameters (T , V z , and λ z ) are in agreement with those found by Klausner et al (2009). The UT of such signatures suggests that for these cases GWs are excited by the solar terminator passage (Somsikov and Ganguly, 1995;Galushko et al, 1998). On the other days, not characterized by RSF occurrence (Fig.…”
Section: Discussion and Summarysupporting
confidence: 86%
“…The obtained results concerning the LS structure agree with theoretical indications of ST effects (Cot and Teitelbaum, 1980;Somsikov, 1983Somsikov, , 1987Somsikov and Ganguly, 1995;Dungenbaeva and Ganguly, 2004;Antonova et al, 2006) and do not contradict the experimental results obtained by Mishin et al (1991), Beley et al (1995), and Galushko et al (1998Galushko et al ( , 2003. In particular, these results confirm the conclusion by Galushko et al (1998) that ST-generated AGWs can be observed at sunrise better than at sunset (corresponding data will be presented in future publications). Using the GPS/MET observation at heights from 300 to 600 km, Hocke and Igarashi (2002) found the LS structure that may result from the disturbance Fig.…”
Section: Discussionsupporting
confidence: 81%
“…The great variety of ST-linked phenomena in the atmosphere has resulted in a number of studies being carried out on the analysis of ionosphere parameter variations obtained by different methods of ionosphere sounding (Bezrodny and Yampolski, 1976;Popov and Yampolski, 1981;Galushko and Yampolski, 1983;Mishin et al, 1991;Drobzhev et al, 1992;Bezotosnyi et al, 1994;Beley et al, 1995;Sobral et al, 1997;Galushko et al, 1998;Hocke and Igarashi, 2002;Galushko et al, 2003). However, virtually all experimental data were obtained using indirect methods for analyzing the spectrum of ionosphere parameter variations, which can result from a number of factors.…”
Section: Introductionmentioning
confidence: 99%
“…At nighttime, the LS-TIDs were found more often regardless of the K-index. Galushko et al [1998] observed TIDs which would be generated by the moving solar terminator. They reported characteristics of the observed TIDs: propagation velocity of 300 -400 m/s corresponding to the solar terminator speed at the ionospheric height, period of 1.5 -2 hours, and propagation direction perpendicular to the solar terminator.…”
Section: Introductionmentioning
confidence: 99%